2017
DOI: 10.1111/1471-0528.14690
|View full text |Cite
|
Sign up to set email alerts
|

Self‐management of first trimester medical termination of pregnancy: a qualitative study of women's experiences

Abstract: ObjectiveTo explore the experiences of women in Scotland who return home to complete medical termination of pregnancy (TOP) ≤63 days of gestation, after being administered with mifepristone and misoprostol at an NHS TOP clinic.DesignQualitative interview study.SettingOne National Health Service health board (administrative) area in Scotland.Population or SampleWomen in Scotland who had undergone medical TOP ≤63 days, and self‐managed passing the pregnancy at home; recruited from three clinics in one NHS health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 30 publications
(79 reference statements)
3
57
0
Order By: Relevance
“…The datasets were produced in England and Scotland, respectively, and have generated a substantial literature [15][16][17][18][19][20][21][22]. They comprised 60 one-to-one interviews with health professionals working in abortion care or referral, including nurses, clinical support workers (CSWs), doctors and clinic managers.…”
Section: Methodsmentioning
confidence: 99%
“…The datasets were produced in England and Scotland, respectively, and have generated a substantial literature [15][16][17][18][19][20][21][22]. They comprised 60 one-to-one interviews with health professionals working in abortion care or referral, including nurses, clinical support workers (CSWs), doctors and clinic managers.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative research from Scotland among women living in Edinburgh and the surrounding region who had an early medical abortion (EMA) demonstrated high social acceptability of EMA at home, yet the women reported that they would benefit from abortion services being even more accessible 6. Other research among women in a remote and rural part of Scotland found that alongside travel difficulties faced when accessing abortion care, stigma surrounding abortion and anticipation of a traumatic experience also deterred women from seeking abortion care 7.…”
Section: Introductionmentioning
confidence: 99%
“…This was commonly self-administered by women in the clinic,5–7 after which they went home to abort the pregnancy. Women found these extra visits inconvenient and reported distressing bleeding or pain on their journey home due to the onset of action of misoprostol 8 9. In October 2017, the Scottish government introduced legislation rendering the home use of misoprostol for EMA legal 10.…”
Section: Introductionmentioning
confidence: 99%